1988
DOI: 10.1002/ddr.430140208
|View full text |Cite
|
Sign up to set email alerts
|

Ocular hypotensive effects of lofexidine, an alpha2‐adrenoreceptor agonist

Abstract: The present study examines the ocular hypotensive efficacy end pupillary response of the alpharadrenergic receptor agonists lofexidine and clonidine. The topical administration of lofexidine to rabbit eyes in concentrations ranging from 0.25 to 5%, produced a dosedependent bilateral reduction in intraocular pressure (IOP), with the contralateral (untreated) eye exhibiting a significantly greater reduction in IOP than the ipsilateral (treated) eye, particularly at the lower concentrations. The maximum decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
(3 reference statements)
2
5
0
Order By: Relevance
“…This phenomenon has been reported for other 0C2-agonists, e.g. lofexidine (6), UK-14,304-18 (1) and moxonidine (4). It was proposed that the delayed ipsilateral IOP response was possibly due to competing activities at peripheral postjunctional (contraction of the extraocular muscle) and prejunctional (sympathetic nerve ending) sites (1).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This phenomenon has been reported for other 0C2-agonists, e.g. lofexidine (6), UK-14,304-18 (1) and moxonidine (4). It was proposed that the delayed ipsilateral IOP response was possibly due to competing activities at peripheral postjunctional (contraction of the extraocular muscle) and prejunctional (sympathetic nerve ending) sites (1).…”
Section: Discussionsupporting
confidence: 77%
“…Similar properties for clonidine have been reported in the rabbit ciliary process (10). In our previous work with other cc2-agonists, it has been shown that the ranked order of intrinsic activity at inhibiting isoproterenol-stimulated adenylate cyclase was lofexidine = p-amino-clonidine > clonidine (11) and clonidine had a lower intrinsic activity at lowering IOP than lofexidine in normotensive rabbits (6). Similarly, it was found that detomidine had a lesser maximum effect than medetomidine both in lowering IOP and inhibiting adenylate cyclase activity in this experiment.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The a2-adrenergic agonists (B-HT920, B-HT 933, UK-14,308-18, clonidine, lofexidine) have been reported to lower intraocular pressure (IOP) in experimental animals and in humans (1)(2)(3)(4)(5). Innemee et al, (1) demonstrated that cc2-adrenoceptor agonists are generally more effective ocular hypotensive agents than ai-agonists in laboratory animals.…”
Section: Introductionmentioning
confidence: 99%